2020
DOI: 10.1093/geront/gnaa165
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Health Care and Employment Resources During COVID-19: Roles of Benevolent and Hostile Ageism

Abstract: Background and Objectives Benevolent and hostile ageism are subtypes of ageism that characterize older adults as incompetent. With benevolent ageism, older adults are also viewed as warm. The COVID-19 pandemic has strained resources and prompted debates about priority for older adults versus other groups. Research Design and Methods College students completed an online survey of how much priority should be given to older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…Besides, while we assessed perceived ageism in different domains, which is a strength, the questions were not used in previous studies and did not allow for the differentiation of hostile and benevolent forms of ageism (e.g., the well-meant take-over of chores, regardless of people's capacities and wishes). Benevolent ageism might negatively affect people's autonomy and self-worth on a more implicit and long-term level ( 35 , 36 ) and thus both forms of ageism and their effects on people's self-perceptions of aging need to be addressed in future studies [cf. ( 9 )].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, while we assessed perceived ageism in different domains, which is a strength, the questions were not used in previous studies and did not allow for the differentiation of hostile and benevolent forms of ageism (e.g., the well-meant take-over of chores, regardless of people's capacities and wishes). Benevolent ageism might negatively affect people's autonomy and self-worth on a more implicit and long-term level ( 35 , 36 ) and thus both forms of ageism and their effects on people's self-perceptions of aging need to be addressed in future studies [cf. ( 9 )].…”
Section: Discussionmentioning
confidence: 99%
“…Ageism, in part, may account for the sluggish and inadequate response to the COVID-19 pandemic, resulting in negative physical and mental health consequences for older adults ( Ayalon, 2020 ; Ayalon et al, 2020 ; Bergman et al, 2020 ; Monahan et al, 2020 ). Given the potential for the COVID-19 pandemic to affect future behavior toward older adults ( Apriceno et al, 2020 ), this two-part study sought to examine whether pre-pandemic views of older adults predicted prosocial behavioral intentions specific to the pandemic and more generally. This timely study examined undergraduates, a population that has reported ageism in prior studies ( Apriceno et al, 2020 ; Bousfield & Hutchison, 2010 ; Kite et al, 2005 ; Lytle, Macdonald et al, 2020 ).…”
mentioning
confidence: 99%
“…Given the potential for the COVID-19 pandemic to affect future behavior toward older adults ( Apriceno et al, 2020 ), this two-part study sought to examine whether pre-pandemic views of older adults predicted prosocial behavioral intentions specific to the pandemic and more generally. This timely study examined undergraduates, a population that has reported ageism in prior studies ( Apriceno et al, 2020 ; Bousfield & Hutchison, 2010 ; Kite et al, 2005 ; Lytle, Macdonald et al, 2020 ).…”
mentioning
confidence: 99%
“…Older people are associated with debilitation, they are deemed not worthy of attention, non-competitive or unsuitable for employment, although warm (Chang et al 2020;Cherry and Palmore 2008;Cuddy et al 2005). Thus, ageism can be both benevolent and hostile (Apriceno et al 2020). Unfortunately, these stereotypes are largely consistent across cultures and they most often result in social exclusion (Inglehart et al 2014;Stuckelberger et al 2013;Walsh et al 2017).…”
Section: The Impact Of Covid-19 Risk Mitigation Measures On Older Adults' Well-beingmentioning
confidence: 99%